2020
DOI: 10.1027/1015-5759/a000547
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Report Symptom Inventory as an Instrument for Detecting Symptom Over-Reporting

Abstract: Abstract. The recently developed Self-Report Symptom Inventory (SRSI) intends to provide an alternative approach to the detection of symptom over-reporting. Unlike other measures, the SRSI includes both non-existent symptoms (i.e., pseudosymptoms) and genuine symptoms. Previous research using the German SRSI showed that people who exaggerate their complaints over-endorse both types of symptoms. In the current simulation experiment, we tested whether the Dutch and English SRSI are effective in identifying over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Thus, no differences were found between truth tellers and malingerers, nor exaggerators and malingerers in terms of genuine symptoms and pseudosymptoms. These findings are unusual, considering repeated findings that support malingerers' "over-the-top" strategy of endorsing symptoms (Boskovic, Merckelbach, et al, 2019;Merten et al, 2016). In this study, however, it was shown that, although both exaggerators and malingerers exhibited over-reporting, this tendency was slightly stronger among exaggerators, who had an underlying genuine condition that led to a significant difference only between exaggerators and truth tellers.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Thus, no differences were found between truth tellers and malingerers, nor exaggerators and malingerers in terms of genuine symptoms and pseudosymptoms. These findings are unusual, considering repeated findings that support malingerers' "over-the-top" strategy of endorsing symptoms (Boskovic, Merckelbach, et al, 2019;Merten et al, 2016). In this study, however, it was shown that, although both exaggerators and malingerers exhibited over-reporting, this tendency was slightly stronger among exaggerators, who had an underlying genuine condition that led to a significant difference only between exaggerators and truth tellers.…”
Section: Discussioncontrasting
confidence: 67%
“…In this project, we followed a between-groups design using a simulation paradigm, meaning that participants received instructions in the form of vignettes to simulate a certain condition. Both the SRSI and the VA have been used in simulation design studies (see Boskovic et al, 2017;Boskovic, Dibbets, et al, 2019;Boskovic, Merckelbach, et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations